2010
DOI: 10.1007/s10393-010-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Promotes the Emergence of Serious Disease Outbreaks of Filarioid Nematodes

Abstract: Filarioid parasites represent major health hazards with important medical, veterinary, and economic implications, and considerable potential to affect the everyday lives of tens of millions of people globally (World Health Organization, 2007). Scenarios for climate change vary latitudinally and regionally and involve direct and indirect linkages for increasing temperature and the dissemination, amplification, and invasiveness of vector-borne parasites. High latitude regions are especially influenced by global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 35 publications
0
69
0
1
Order By: Relevance
“…Emerging diseases are of increasing global importance, and are also of considerable concern for northern ungulates (Kuiken et al, 2003;Kutz et al, 2004;Laaksonen et al, 2010). Northward range expansion of domestic and wild animals, together with various pathogen vectors, may allow introduction of new pathogens into Rangifer range.…”
Section: Carma Network Feedback and Protocol Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging diseases are of increasing global importance, and are also of considerable concern for northern ungulates (Kuiken et al, 2003;Kutz et al, 2004;Laaksonen et al, 2010). Northward range expansion of domestic and wild animals, together with various pathogen vectors, may allow introduction of new pathogens into Rangifer range.…”
Section: Carma Network Feedback and Protocol Evaluationmentioning
confidence: 99%
“…Northward range expansion of domestic and wild animals, together with various pathogen vectors, may allow introduction of new pathogens into Rangifer range. Concurrently, a warming climate is removing some of the environmental constraints on existing arctic pathogens, resulting in range expansion of pathogens and emergence of disease (Hoberg et al, 2008;Kutz et al, 2009;Laaksonen et al, 2010). Establishing comprehensive baselines for pathogen biodiversity and abundance is necessary if we are to detect emergence of new pathogens and disease syndromes.…”
Section: Carma Network Feedback and Protocol Evaluationmentioning
confidence: 99%
“…Studies of ptarmigan parasite loads have revealed a wide variety of blood parasites, including those transferred by mosquito vectors (Holmstad et al 2003), the prevalence of which is expected to increase with warming. There is evidence even now of increased outbreaks of mosquito-borne filaroid nematodes among ungulates in subarctic Fennoscandia, and with apparent demographic consequences (Laaksonen et al 2010). Mosquito habitats may multiply with increased rain and melting permafrost, and the lengthening summers may allow greater development and plasticity within the life cycles of many parasites and pathogens, promoting their prevalence, transmission, and the diversity and longevity of their vectors (see Laaksonen et al 2010).…”
Section: -Hunt -mentioning
confidence: 99%
“…There is evidence even now of increased outbreaks of mosquito-borne filaroid nematodes among ungulates in subarctic Fennoscandia, and with apparent demographic consequences (Laaksonen et al 2010). Mosquito habitats may multiply with increased rain and melting permafrost, and the lengthening summers may allow greater development and plasticity within the life cycles of many parasites and pathogens, promoting their prevalence, transmission, and the diversity and longevity of their vectors (see Laaksonen et al 2010). Bennett et al (1992) reported that blood parasites were "…virtually absent in bird species nesting in the open tundra," with the inference that vectors were lacking, and one wonders what their predicted arrival may portend for avian populations.…”
Section: -Hunt -mentioning
confidence: 99%
“…Filarioid nematode parasites affect millions of people and animals worldwide, and represent a major health hazard with significant economic implications (Laaksonen et al, 2010). Canine dirofilariosis is a major veterinary health problem in tropical, subtropical and temperate regions of the world (Simón et al, 2012), with at least 70 species of mosquitoes being considered as potential vectors .…”
Section: Introductionmentioning
confidence: 99%